2015
DOI: 10.4049/jimmunol.1403135
|View full text |Cite
|
Sign up to set email alerts
|

IL-7/IL-7 Receptor Signaling Differentially Affects Effector CD4+ T Cell Subsets Involved in Experimental Autoimmune Encephalomyelitis

Abstract: IL-17-producing CD4+ T (Th17) cells, along with IFN-gamma-expressing Th1 cells, represent two major pathogenic T cell subsets in experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis (MS). The cytokines and transcription factors involved in the development and effector functions of Th1 and Th17 cells have been largely characterized. Among them, IL-23 is essential for the generation of stable and encephalitogenic Th17 cells and for the development of EAE. The IL-7/IL-7R signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…Selectin–selectin ligand interactions, on the other hand, are dispensable for the development of EAE . Numerous findings support the view that Th17 cells play an essential role in triggering the initial phases of autoimmune CNS inflammation, whereas Th1 cells likely contribute to pathogenesis later in disease progression . Although different T‐cell subsets use a similar repertoire of ligands to traffic to sites of inflammation, their expression patterns can differ, resulting in selective recruitment .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Selectin–selectin ligand interactions, on the other hand, are dispensable for the development of EAE . Numerous findings support the view that Th17 cells play an essential role in triggering the initial phases of autoimmune CNS inflammation, whereas Th1 cells likely contribute to pathogenesis later in disease progression . Although different T‐cell subsets use a similar repertoire of ligands to traffic to sites of inflammation, their expression patterns can differ, resulting in selective recruitment .…”
Section: Introductionmentioning
confidence: 84%
“…[6][7][8] Numerous findings support the view that Th17 cells play an essential role in triggering the initial phases of autoimmune CNS inflammation, whereas Th1 cells likely contribute to pathogenesis later in disease progression. 1,[9][10][11] Although different T-cell subsets use a similar repertoire of ligands to traffic to sites of inflammation, their expression patterns can differ, resulting in selective recruitment. 4,12 Hence, it is critical to identify the adhesion molecules that mediate such selective recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that regulation of IL‐7/IL‐7R signaling pathway may be a new therapeutic strategy for RPL. IL‐7 is a key modulator for the differentiation of effector T cells, especially inducing Th17 cell proliferation in autoimmune diseases, such as autoimmune encephalitis and MS . Recent clinical trials using recombinant IL‐7 have shown an IL‐7‐dose‐dependent increase in CD8 + and CD4 + T cell numbers, but a relative decrease in CD4 + Treg cells .…”
Section: Discussionmentioning
confidence: 99%
“…IL‐7 is a key cytokine which is required for the proliferation and survival of pathogenic Th17 cells and as such has been shown to promote autoimmune diseases, for instance, experimental autoimmune encephalomyelitis (EAE) and multiple sclerosis (MS) . In autoimmune diseases mouse model, blockade of IL‐7R by IL‐7R antagonist prevented Th17 cell differentiation that led to decreased severity of arthritis, reduced joint damage, and decreased pro‐inflammatory cytokines and other mediators associated with tissue damage .…”
Section: Introductionmentioning
confidence: 99%
“…Also, T-helper type 1 (Th1) cells, characterized by the production of interferon gamma (IFN-γ), are considered a type of effector Th cell that mediates the pathogenesis of MS [24]. Th17 cells are at least as crucial as Th1 cells in this disease [25,26].…”
Section: Introductionmentioning
confidence: 99%